Direct marketing like one of the most effective way to increase sales - Kochmaruk, Maria (My University, 2014)
Direct marketing is a sometimes controversial sales method through which advertisers approach potential customers directly with products or services. The most common forms of direct marketing are telephone sales, solicited or unsolicited emails, and mailed catalogs, leaflets, brochures and coupons. In most cases, the goal is to inform customers of products or services that they may need without waiting for customers to initiate contact. Particularly online, the practice has received a lot of criticism when it comes to personal privacy and data tracking. The practice is nevertheless very successful, however, which motivates many marketers to continue despite the possible risks and downsides.
Keywords: increase sales; marketers; marketing; збільшення продажів; маркетологи; маркетинг; увеличение продаж